Jupyter Notebook: система интерактивных научных вычислений - Якимчик, А.И. (Геофизический журнал, 2019)
Jupyter Notebook ― is a web-appendix which allows writing and supplying comments a code to Python in interactive regime. It is an exclusive method to make experiments and studies and intercommunicate with others. Many research people use this calculative medium in their works more often. The main factors of growing popularity of programming language Python and project Jupyter are characterized in brief. Jupyter Notebook ― веб-додаток, що дає змогу писати і постачати коментарями код на мові Python в інтерактивному режимі, а також спосіб експериментувати, досліджувати і ділитися своїми результатами з іншими. Все частіше багато дослідників використовує у своїх роботах зазначене обчислювальне середовище. У короткій формі висвітлено основні причини зростаючої популярності мови програмування Python і проекту Jupyter. Jupyter Notebook - веб-приложение, которое позволяет писать и поставлять комментариями код на языке Python в интерактивном режиме, а также способ экспериментировать, исследовать и делиться своими результатами с другими. Все чаще многие исследователи использует в своих работах указано вычислительную среду. В краткой форме изложены основные причины растущей популярности языка программирования Python и проекта Jupyter.